2019
DOI: 10.15548/mej.v2i2.182
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Pembelajaran Kooperatif Tipe Think Talk Write Terhadap Kemampuan Penalaran Matematis Siswa Kelas XI IPA MAN Kota Padang

Abstract: The problems that occur in the field is the low of students’ mathematical reasoning abilities in the class XI IPA MAN Padang. It can be seen from the finding of observation and analysis toward the result of test given to the students. To overcome the problems, the cooperative teaching model Think Talk Write is used. The purpose of the study is to find out the effct of the cooperative teaching model Think Talk Write application toward students’ mathematical reasoning abilities in the class XI IPA MAN Padang. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The articles on the application of the Think Talk Write (TTW) type cooperative learning model in students' mathematical reasoning abilities are in table 1 below: In the first article, (Irwan & Permata Sari, 2018) conducting research activities regarding the application of the Thing Talk Write (TTW) type cooperative learning model to mathematical reasoning abilities, they conducted research on MAN students of class XII science in the city of Padang. Researchers see the low mathematical reasoning ability of MAN Padang city students from the average UN score obtained is still very low.…”
Section: Articles -Articles Of Mathematical Reasoning Ability Through...mentioning
confidence: 99%
See 2 more Smart Citations
“…The articles on the application of the Think Talk Write (TTW) type cooperative learning model in students' mathematical reasoning abilities are in table 1 below: In the first article, (Irwan & Permata Sari, 2018) conducting research activities regarding the application of the Thing Talk Write (TTW) type cooperative learning model to mathematical reasoning abilities, they conducted research on MAN students of class XII science in the city of Padang. Researchers see the low mathematical reasoning ability of MAN Padang city students from the average UN score obtained is still very low.…”
Section: Articles -Articles Of Mathematical Reasoning Ability Through...mentioning
confidence: 99%
“…And for the analysis of the final ability test data, it was found that the control class students were lower than the experimental class. (Irwan & Permata Sari, 2018) In the second article, Siti Jami'atun and Kristina (2020) conducted research on seventh grade students of SMP in Semarang city in the 2018/2019 academic year. In this study, 2 samples were used, namely the experimental class and the control class.…”
Section: Articles -Articles Of Mathematical Reasoning Ability Through...mentioning
confidence: 99%
See 1 more Smart Citation